Assessment of microwave-assisted pretreatments for enhancing pineapple waste delignification - Nur Izyan, Wan Azelee; Syafiqah Athirah, Mohd Adnan; Nor Hasmaliana, Abdul Manas; Dailin, Daniel Joe; Aizi Nor Mazila, Ramli; Rosli, Md. Illias (AIP Publishing, 2019)
Biological degradation of biomass for the production of fine chemicals is getting much interest nowadays. However, the complex and recalcitrance structure of the biomass hinders the success story of the degradation. Lignin is the main composition that impedes the bioconversion of biomass. Hence, an optimize delignification pretreatment need to be developed to enable the biological degradation process becomes much easier and thus higher production yield can be achieved afterwards. This study focuses on the assessment of pineapple waste (PW) delignification by applying microwave radiation on two different pretreated PW to facilitate the processes. The PW was initially pretreated with distilled water (dH2O) and peracetic acid (PAA) prior to the microwave radiation. Three main parameters (pretreatment time, min; temperature, °C; and microwave radiation power, W) were studied towards the effect of PW delignification. Lignin percentage before and after the pretreatments were compared and analysed. The results obtained revealed that the microwave-assisted PAA shows the best percentage of delignification compared to the microwave-assisted dH2O pretreatment. The best delignification process obtained in this study is a key indicator for a better biomass degradation to achieve higher yield of products in the future.